High-skilled return migration and knowledge-based economic development in regional perspective: Conceptual considerations and the example of Poland - Britta Klagge; Katrin Klein-Hitpaß (University of Warsaw, Centre of Migration Research (CMR), 2007)
It is by now well known that return migration of the highly skilled can have a significant impact on knowledge-based development in the regions to which they return. Whereas previous research has mainly focussed on developing and newly industrializing countries this paper looks at high-skilled return migration in an East European transition economy, namely Poland. The Polish example illustrates that institutional context and the regional dimension are crucial in understanding how high-skilled return migrants do or do not make use of and transform their knowledge and other resources (incl. financial and social capital) and stimulate knowledge-based development. In previous studies, however, these aspects have not been systematically explored or integrated into conceptual thinking. We address this deficit by proposing a micro-level model of high-skilled return migration and economic development. Our model integrates regional economic development and migration theory perspectives into a coherent interdisciplinary framework. We argue that institutional aspects have to be linked to return migrants' individual motivations and other characteristics, and that there are different types of both return migrants and institutional, and regional, contexts. An important feature of our model is the key role assigned to the idea of return migrants' social capital performing a 'bridging function' between actors in the same, but especially in different regions. We claim that our model can serve as basis to empirically analyse and explain whether and how different regional contexts are providing opportunities or posing barriers for migration-induced knowledge-based development. We illustrate and substantiate this proposition by analyzing return migration to Poland.
Keywords: 330; Hochqualifizierte Arbeitskräfte; Rückwanderung; Regionalentwicklung; Polen